THE MILITARY FORCE AND ITS STRUCTURE DURING THE KARAKHANIDS PERIOD - Toshtemirova Sevinch (Web of Journals Publishing, 2026)
This article analyzes the formation, structure, and development stages of the military system of the Karakhanid State in the 9th–12th centuries. The study examines the composition of the army, hierarchy of military ranks, combat tactics, defensive structures, and the state’s military-political strategy. The Karakhanids’ military strength was formed through the integration of Turkic nomadic traditions with the military experience of settled regions, as evidenced by historical sources. The article highlights the role of the military system in ensuring state stability and territorial expansion, as well as its significance in the military history of Central Asia.
Keywords: Karakhanids, military system, combat tactics, hierarchy, defense, Central Asia.